Robot Authority in Human-Robot Teaming: Effects of Human-Likeness and Physical Embodiment on Compliance - Haring, Kerstin S.; Satterfield, Kelly M.; Tossell, Chad C.; de Visser, Ewart J.; Lyons, Joseph R.; Mancuso, Vincent F.; Finomore, Victor S.; Funke, Gregory J. (Frontiers in Psychology, 2021)
The anticipated social capabilities of robots may allow them to serve in leading roles as part of human-machine teams. Robots will be expected to work effectively with their human counterparts. To date, it is unclear if, and to what extent, human team members will comply with requests from their robotic teammates, and how such compliance compares to requests from their human teammates. In this research effort, we examined how the human-likeness and physical embodiment of a robot affect compliance to a robot’s request to perseverate at a task. Across a set of two studies, participants performed a visual search task while receiving ambiguous performance feedback. Compliance was evaluated when the participant requested to stop the task and the coach urged the participant to keep practicing multiple times. In the first study, the coach was either physically co-located with the participant or located remotely where interaction occurred via a live-video. Coach type varied in human-likeness and included either a real human (confederate), a Nao robot, or a Roomba robot. The second study expanded on the first by including a Baxter robot as a Coach and replicated the findings in a sample population with a strict chain of command culture. Results from both studies indicate that participants will comply with th